Feminist and Lingvostylistic Paradigms in Virginia Woolf’s „A Room of One’s Own“ - Danelia, Ira; Tsurtsumia, Koba (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
This publication discusses the theoretical work „A Room of One's Own“ by Virginia Woolf, a British writer, essayist, and outstanding representative of modernist literature. The work also presents the visions of European and American women intellectuals and their theoretical works, which called for a fundamental transformation to improve women's rights and opportunities in women's lives, society, and the family. The work aims to provide a complex understanding of anti-feminist and anti-gender issues. At the same time, it discusses the most important issues and challenges faced by intellectual women in general. Lingvostylistic characteristic of feminist literature are emphasized in the present article, in particular, on the example of Virginia Woolf'’s "A Room of One's Own", as this work of hers is less studied in this regard.This is the goal and novelty of our paper work from the linguistic and stylistic point of view. The abovementioned article seeks to deepen our understanding of Woolf’ 's feminist message and the literary techniques she used to convey it by analyzing the essay's language and style through a feminist lens. This feminist stylistic analysis can help to uncover how Virginia Woolf used language to challenge traditional ideas of gender and promote gender equality. So she made room indeed for the next generation of women writers and critics. Misogyny, mistrust, hatred towards women, and humiliation continued for a long time. In the "black and dark" era, it was unacceptable to talk about women's freedom, economic stability, participation in elections, education, including in literature. For centuries, women sacrificed to patriarchal thinking. The old patriarchal ideology begins to break down at the turn of the 20th and 21st centuries. Today, in the scientific literature, the term "feminism" has become a key word. The following research methods are used in the article: source knowledge method, data collection-processing method, critical analysis method, linguostylistic analysis method, and observation method.